Peran Mediasi Komitmen Organisasi pada Pengaruh Kompetensi dan Budaya Organisasi Terhadap Kinerja Pegawai - Darto Wahab; Euis Soliha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The performance of human resources in the health sector still show problems with the quality of work results. Beside, the challenges ahead are getting tougher, especially in facing global diseases and technological advances. This study aims to examine the influence of competence and organizational culture on employee performance mediated by organizational commitment. The research method uses a quantitative approach with 104 employees as respondents at the Demak Regency Health Office, Central Java, Indonesia. Survey data were analyzed using descriptive statistics, multiple linear regression, path analysis, and the Sobel test. The findings revealed that competence and organizational culture have a positive effect on organizational commitment. However, the opposite result is that competence does not have a significant effect on employee performance, while organizational culture and organizational commitment have been shown to contribute positively. The conclusion states that competence and organizational culture have been proven to be determinant factors for employee performance, with organizational commitment acting as an intervening variable. The managerial implication is that the application of organizational culture values including professionalism, accountability, enthusiasm, non-discrimination, and integrity should continue to be improved.